Rancang Bangun Sistem Penilaian Kinerja Karyawan (Studi Kasus Cleaning Section Pt. Ume Sembada Gresik) - Rachmawati, Anandya Sofa; Supriyanto, Antok; Sulistiowati, Sulistiowati (Jurnal JSIKA, 2012)
PT. Ume Sembada Gresik is a company that supplied the field of outsourced labor. The quality of human resources is one of the important factors to improve the productivity of the company´s performance. PT. Ume Sembada Gresik strive to improve the quality of the company to conduct an evaluation / assessment of performance in a way that is still manual. Performance appraisal system needs to be developed in the PT. Ume Sembada Gresik so as to assist in the performance appraisal problems. performance appraisal systems in this company are implemented using the Preference Ranking Organization Method For Enrichment Evaluation (Promethee) as determining the rankings. This method is part of meode Multiple Criteria Decision Making (MCDM). With Promethee methods, assessment of an employee will be assessed taking into account the differences between the criteria for each employee to another employee. Based on the results of the implementation and testing of systems, employee performance appraisal system on PT. Ume Sembada Gresik to result in any employee performance appraisals faster than manual calculation. These results can be demonstrated by the performance appraisal report. Keyword: Performance appraisal, Multiple criteria, Dcision Making, Preference Rangking, Promethee